Temporal muscle thickness has no prognostic relevance in patients with high-grade glioma compared to functional scales - Klingenschmid, Julia; Krigers, Aleksandrs; Schön, Victoria; Pinggera, Daniel; Kerschbaumer, Johannes; Grams, Astrid E.; Thomé, Claudius; Freyschlag, Christian F. (Frontiers in Oncology, 2023)
Background: GBM research is constantly assessing potential valuable prognostic biomarkers to better understand the disease and prognosticate future outcomes. Measuring temporalis muscle thickness (TMT) has appeared to be a promising new surrogate marker for skeletal muscle mass and sarcopenia, which further indicates frailty and predicts overall survival (OS). The aim of this study was to determine its usefulness as a prognostic marker in patients with high-grade glioma compared to functional status scales.Methods: TMT was measured in preoperative axial T1 weighted contrast enhanced magnetic resonance images in 277 patients who received surgical treatment of newly diagnosed WHO III and IV gliomas in our institution between 2015 and 2020. Clinical frailty scale (CFS) and Karnofsky performance score (KPS) were assessed preoperatively and during a follow-up visit.Results: Female gender has shown significant correlation with TMT, while TMT did not correlate with preoperative and follow-up functional scores, age, WHO classification, IDH mutation, MGMT promotor methylation, EGFR and ATRX expression or 1p/19q co-deletion. No significant prognostic value of TMT could be shown in 6, 12 and 24 months OS, while changes in CFS and KPS proved to have a significant impact.Conclusions: Only female gender, but no other clinical, histological or molecular marker showed any interrelation with TMT. Functional scores outclass measuring TMT as a reliable prognostic factor for predicting OS in patients with high-grade glioma.